Fundamentals of programmable of logic logic controllers,sensor and communications - Stenerson, Jon (Prentice Hall, 1999)
Uses a generic approach to introduce various brands and types of industrial controllers. Since the programmable logic controller has become an invaluable tool in American industry, this book is useful for trained personnel who can program and integrate these devices.